Infection Prevention and Control Practices among Nurses in Selected Health Facilities in Greater Accra Region of Ghana - Ampadu, H. (University of Ghana, 2019)
Background Nurses play a pivotal role in healthcare delivery and they are responsible for ensuring the safety of patients as well as their own safety in the clinical setting. Nurses are in more contact with patients than other healthcare professionals and hold the key to infection prevention and control challenges. Inadequate knowledge and failure of nurses to comply with infection prevention and control (IPC) practices at healthcare settings is a major contributory factor to the burden of healthcare associated infections (HCAIs). Objective The study is aimed at assessing the knowledge, compliance and factors influencing compliance with IPC practices among nurses Method A descriptive cross-sectional study involving 237 nurses from three hospitals in the Greater Accra Region of Ghana was conducted. The hospitals were randomly selected through balloting and proportionate sampling method was used to select nurses from the three hospitals. In the facilities, nurses were conveniently selected to participate in the study if they met the inclusion criteria and gave their consent. Validated standardized questionnaires were used to collect the data. Descriptive statistics and inferential statistics using bivariate analysis (Chi-square and Fisher’s exact test) and multivariable logistics regression were used to analyze the data with the help of Stata IC version 15.0 Results Findings from the study showed that, majority (83.7%) of the nurses had good knowledge of IPC practices in general, however; only 25% and 43% of the nurses were knowledgeable about nosocomial infections and safe injection practices respectively. The study also showed high level (79.1%) of self-reported compliance with IPC practices among nurses. Majority of the nurses (68.4%) reported they recapped needles after use. About 93.5% of the nurses reported they always washed hands with soap under running water in their units, however, only 50% were observed to practice frequent hand wash with soap under running water. Perception of risk of infection measured by vaccination status [AOR= 3.46, 95% CI (1.64, 7.31)] and accessibility to personal protective equipment (PPE) [(AOR=2.13, 95% CI (1.06, 4.27)] were factors found to be significantly associated with compliance with IPC practices. Conclusion The study revealed that the level of knowledge and compliance of nurses with IPC practices were generally good. However, there were some lapses in knowledge and compliance with respect to the various IPC procedures and what was observed in practice. Health institutions need to intensify training and education on the various IPC procedures to achieve complete and accurate IPC practices in the clinical settings for safe healthcare delivery. There is the need for larger observational studies using observational checklist to ascertain compliance with IPC practices.
MPH.
Keywords: Infection Prevention and Control (IPC); Infections; Hygienic Hand Practice